Nanosized Contrast Agents in Ultrasound Molecular Imaging - Zeng, Fengyi; Du, Meng; Chen, Zhiyi (Frontiers in Bioengineering and Biotechnology, 2021)
Applying nanosized ultrasound contrast agents (nUCAs) in molecular imaging has received considerable attention. nUCAs have been instrumental in ultrasound molecular imaging to enhance sensitivity, identification, and quantification. nUCAs can achieve high performance in molecular imaging which was influenced by synthetic formulations and size. This review presents an overview of nUCAs from different synthetic formulations with a discussion on imaging and detection technology. Then we also review the progress of nUCAs in preclinical application and highlight recent challenges of nUCAs.